EVALUASI PROYEK PEMBANGUNAN PASAR UMUM (MERCADO GERAL) FOMENTO MANLEUANA Studi Pasar Umum (mercado geral) Fomento Manleuana Kecamatan (sub distrito) Dom Alexo Kabupaten (distrito) Dili Timor Leste - , RUBEN LIMA SANTOS PIRES, Dr. Ertambang Nahartyo, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to measure the effectiveness of the implementation of development projects market (mercado) Fomento Manleuana general and measure the cost (cost), social benefits (social benefits) are expected by the society after the development of the market. Data used in this study consists of primary data and secondary data using qualitative analysis methods. Analysis tools used are focus group discussions (focused group discussion, FGD) and SWOT analysis (strengths, weaknesses opportunities, threats). Planning and market development is carried out by the government since 2009 and will end in May 2012. The total budget is used for the construction market was U.S. $3,632,099.05 (three million six hundred and thirty-two thousand, ninety-nine and fifty dollars Unites States Dollars). Market development objective is to increase the income level of low-income communities and create employment to the people who work as traders in the district of Dili District Alexo Dom Timor Leste. The results showed that the economic prospects for the future development of the market (mercado) Fomento Manleuana benefit society generally. However, the implementation process of market development project implemented not through a feasibility study (feasibility study). This is caused by various problems